Suppression of Bromus tectorum L. by Established Perennial Grasses: Potential Mechanisms—Part One - Robert R. Blank; Tye Morgan (Applied and Environmental Soil Science)
Bromus tectorum L. (cheatgrass) is an Eurasian annual grass that has invaded ecosystems throughout the Intermountain west of the United States. Our purpose was to examine mechanisms by which established perennial grasses suppress the growth of B. tectorum. Using rhizotrons, the experiment was conducted over 5 growth cycles: (1) B. tectorum planted between perennial grasses; (2) perennials clipped and B. tectorum planted; (3) perennials clipped and B. tectorum planted into soil mixed with activated carbon; (4) perennials clipped, B. tectorum planted, and top-dressed with fertilizer, and; (5) perennial grasses killed and B. tectorum planted. Water was not limiting in this study. Response variables measured at the end of each growth cycle included above-ground mass and tissue nutrient concentrations. Relative to controls (B. tectorum without competition), established perennial grasses significantly hindered the growth of B. tectorum. Overall, biomass of B. tectorum, grown between established perennials, increased considerably after fertilizer addition and dramatically upon death of the perennials. Potential mechanisms involved in the suppression of B. tectorum include reduced nitrogen (possibly phosphorus) availability and coopting of biological soil space by perennial roots. Our data cannot confirm or reject allelopathic suppression. Understanding the mechanisms involved with suppression may lead to novel control strategies against B. tectorum.